The Sign Found in The Movie “Mr Harrigan’s Phone” - Ni Nyoman Puteri Antari; I Gusti Ngurah Adi Rajistha; A.A Istri Manik Warmadewi (PRAGMATICA : Journal of Linguistics and Literature, 2023)
The title of this research is “The Sign Found in The Movie Mr Harrigan’s Phone”. This research has difference with the other previous. Previous research was analyzing kind and function. This research analyzes types and meaning by Peirce and Barthes. Previous research used action, adventure, and fantasy movie genres. This reseach used horror and drama genres. The purpose of this research are observe and provide information to readers about the types and inform the meanings contained in the movie "Mr. Harrigan's Phone". Therefore this research can inform the reader's about sign systems contained in the movie “Mr. Harrigan's Phone” and this research can be expected a reference for readers as to learn the sign. This research used qualitative method by Creswell to analyze the data. This research has 2 problems. The first is type used Peirce's theory. Peirce has three types of signs namely icon, index, and symbol. The results of the identification in the Mr Harrigan's Phone movie get 5 icons, 5 indexes and 5 symbols. The second is the meaning. This study used Barthes' theory to identifying meaning. Barthes has 3 system namely denotation, connotation, and myth.